The Effectiveness of the Differentiated Instruction Learning Model in Long Jump Material to Accommodate Differences in Student Learning Styles - Latuheru, Ricardo Valentino (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aims to analyze the effectiveness of the Differentiated Instruction (DI) learning model in accommodating differences in student learning styles in the long jump at SMP Negeri 33 Makassar. The study used a quasi-experimental one-group pretest–posttest design involving 20 students classified into visual, auditory, and kinesthetic learning styles. Data were obtained through long jump technique and jump distance tests before and after the treatment, then analyzed using descriptive statistics, paired sample t-tests, and N-Gain calculations. The results showed a significant improvement in students’ technique and jump distance after implementing the DI model. The average technique score increased from 11.25 to 16.40, while the jump distance increased from 2.85 m to 3.54 m. The N-Gain value of 0.59 indicates moderate improvement, but approaching the high category. Analysis based on learning styles revealed that the visual and kinesthetic groups achieved the greatest improvement, although all learning styles showed significant improvement. These findings confirm that Differentiated Instruction is an effective, adaptive, and inclusive learning strategy in the context of physical education. This model is able to adapt to individual student needs, thereby improving technical understanding, motivation, and long jump performance. This study makes an important contribution to the development of sports learning practices in schools and recommends further research with a more robust experimental design.